First Kasadya-an [videorecoring] Leyte festival of festivals, Ormoc City, May 11-12, 1976 / National Commission for Culture and the Arts. (Travel Time, 1996)
A documentation of the festival. Also performances of the different cultural dances of the province of Leyte.